MOF-derived core-shell structured Cu9S5/NC@Co3S4/NC composite as a high-efficiency electromagnetic wave absorber. Issue 6 (15th March 2023) - Zhu, Huanhuan; Liang, Jie; Jiao, Xiaoguang; Fu, Ruru; Jiao, Qingze; Feng, Caihong; Li, Hansheng; Zhang, Yaoyuan; Zhao, Yun
Abstract: Constructing specific microstructures and designing multicomponent composites are regarded as effective approaches to obtaining high-efficiency electromagnetic (EM) wave absorbing materials. Herein, core-shell structured Cu9 S5 /N-doped carbon@Co3 S4 /N-doped carbon (Cu9 S5 /NC@Co3 S4 /NC) composites derived from Cu3 (BTC)2 @ZIF-67 were synthesized by facile carbonization and sulfidation processes. The Cu9 S5 particles are embedded in the interior and surface of the carbon skeleton, and the Co3 S4 /NC particles are uniformly distributed on the surface of the carbon skeleton. Compared with Cu9 S5 /NC and Co3 S4 /NC, the Cu9 S5 /NC@Co3 S4 /NC composite displays improved impedance matching properties and much better EM wave absorbing properties. The minimum reflection loss (RLmin ) reaches −41.6 dB at 10.52 GHz with a thickness of 2 mm. In addition, the effective absorption bandwidth (EAB, RL < −10 dB) is 4.08 GHz (12.73–16.81 GHz) with un ultrathin thickness of 1.5 mm. This work offers a facile strategy for synthesizing MOF-derived metal sulfides/carbon composites as EM wave absorption materials with strong absorption properties, a wide absorption bandwidth and ultrathin thickness.